The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00221-013-3769-9
|View full text |Cite
|
Sign up to set email alerts
|

The background is remapped across saccades

Abstract: Physiological studies have found that neurons prepare for impending eye movements, showing anticipatory responses to stimuli presented at the location of the post-saccadic receptive fields (RFs) (Wurtz in Vis Res 48:2070-2089, 2008). These studies proposed that visual neurons with shifting RFs prepared for the stimuli they would process after an impending saccade. Additionally, psychophysical studies have shown behavioral consequences of those anticipatory responses, including the transfer of aftereffects (Mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This hypothesis was further supported by several subsequent studies (Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015). However, in recent years a number of studies have provided evidence that feature information, in addition to attentional pointers, is also involved in transsaccadic remapping (Cha & Chong, 2013;Demeyer, De Graef, Wagemans, & Verfaillie, 2009, 2010Demeyer, Graef, Verfaillie, & Wagemans, 2011;Eccelpoel, Germeys, Graef, & Verfaillie, 2008;Edwards, VanRullen, & Cavanagh, 2017;Fracasso, Caramazza, & Melcher, 2010;Gordon, Vollmer, & Frankl, 2008;Habtegiorgis, Rifai, Lappe, & Wahl, 2018;Harrison & Bex, 2014;Hayhoe, Lachter, & Feldman, 1991;He et al, 2017;Herwig & Schneider, 2014;Koller & Rafal, 2018;Melcher, 2007;Nakashima & Sugita, 2017;Oostwoud Wijdenes, Marshall, & Bays, 2015;Paeye, Collins, & Cavanagh, 2017;Prime, Niemeier, & Crawford, 2006;Prime, Vesia, & Crawford, 2011;Sligte et al, 2017;Wittenberg, Bremmer, & Wachtler, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013;Zimmermann et al, 2017;Zimmermann, Weidner, Abdollahi, & Fink, 2016;Zirnsak et al, 2011). Our study is in line with these studies, and further...…”
Section: Remapping Of Features or Attentional Pointers?supporting
confidence: 92%
“…This hypothesis was further supported by several subsequent studies (Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015). However, in recent years a number of studies have provided evidence that feature information, in addition to attentional pointers, is also involved in transsaccadic remapping (Cha & Chong, 2013;Demeyer, De Graef, Wagemans, & Verfaillie, 2009, 2010Demeyer, Graef, Verfaillie, & Wagemans, 2011;Eccelpoel, Germeys, Graef, & Verfaillie, 2008;Edwards, VanRullen, & Cavanagh, 2017;Fracasso, Caramazza, & Melcher, 2010;Gordon, Vollmer, & Frankl, 2008;Habtegiorgis, Rifai, Lappe, & Wahl, 2018;Harrison & Bex, 2014;Hayhoe, Lachter, & Feldman, 1991;He et al, 2017;Herwig & Schneider, 2014;Koller & Rafal, 2018;Melcher, 2007;Nakashima & Sugita, 2017;Oostwoud Wijdenes, Marshall, & Bays, 2015;Paeye, Collins, & Cavanagh, 2017;Prime, Niemeier, & Crawford, 2006;Prime, Vesia, & Crawford, 2011;Sligte et al, 2017;Wittenberg, Bremmer, & Wachtler, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013;Zimmermann et al, 2017;Zimmermann, Weidner, Abdollahi, & Fink, 2016;Zirnsak et al, 2011). Our study is in line with these studies, and further...…”
Section: Remapping Of Features or Attentional Pointers?supporting
confidence: 92%
“…Adaptation paradigms also have the advantage of being able to target specific levels of neural representation in the visual pathway by selectively adapting to properties with different levels of complexity ( Boynton & Finney, 2003 ; Clifford & Rhodes, 2005 ; Georgeson, 2004 ; Kohn, 2007 ; Rushton, 1965 ). In our study, we took advantage of two forms of visual aftereffects that were previously shown capable of generating spatiotopic aftereffects, namely the tilt aftereffect (TAE) and the face gender aftereffect (FGAE) ( Cha & Chong, 2014 ; He, Mo, & Fang, 2017 ; He, Fritsche, & Lange de, 2018 ; Melcher, 2005 , 2009 ; Nakashima & Sugita, 2017 ; Wolfe & Whitney, 2015 ; Zimmermann, Morrone, Fink, & Burr, 2013 ; Zirnsak, Gerhards, Kiani, Lappe, & Hamker, 2011 ). We first verified that both TAE and FGAE could be observed at the spatiotopic location, which implied that the adapting stimulus had undergone retinotopic-to-spatiotopic transformation.…”
Section: Introductionmentioning
confidence: 99%